Analisis Determinan Yang Mempengaruhi Risiko Pembiayaan Mudharabah Pada BPRS Di Indonesia - Aisyah Rain Sinaga; Wilda Sri Munawarah (Jurnal Pemimpin Bisnis Inovatif, 2024)
This research aims to determine the factors that influence the risk of mudharabah financing at Sharia People's Financing Banks (BPRS) in Indonesia. The independent variables used in this research are Ratio Of Assets (ROA), Operational Costs Operational Income (BOPO), Financing To Deposit Ratio (FDR), Capital Adequity Ratio (CAR). The research method used was quantitative, with sampling using purposive sampling consisting of 15 BPRS registered in Indonesia. The results of this research show that the Ratio Of Assets (ROA) variable has a significant positive effect on mudharabah financing risk, Operational Costs Operating Income (BOPO) has an insignificant positive effect on mudharabah financing risk, Financing To Deposit Ratio (FDR) has an insignificant positive effect on financing risk mudharabah, Capital Adequity Ratio (CAR) has an insignificant positive effect on mudharabah financing risk. Based on these results, it is found that the determinant coefficient value is 0.4436, meaning that the variables Ratio Of Assets (ROA), Operational Costs Operational Income (BOPO), Financing To Deposit Ratio (FDR), Capital Adequity Ratio (CAR) can explain the dependent variable, namely risk. mudharabah financing is 44.36% and the remaining 65.64% is explained by other variables or other factors that are not included in this model.